Avaliação da aprendizagem em Ciências da Natureza: uma experiência com o portfólio no Ensino Médio - (:unkn) unknown (Universidade Federal do Pampa, 2023)
With the intention of discussing the topic of learning assessment, specifically the portfolio as a formative assessment tool, justified by the experience as a teacher in training, linked to the inclusive assessment concept and the diversity of assessment strategies that can be used in favor of building meaningful learning. To this end, we seek to answer what are the theoretical-methodological contributions of assessment mediated by the portfolio in high school? The objective of which is to analyze the experience with the portfolio in the disciplines of Chemistry, Physics and Biology, with a 3rd year high school class at a state school in Dom Pedrito. The subjects are 16 students, aged between 19 and 24, mostly workers. Methodologically it is characterized as a research with a qualitative approach, in relation to the objectives it is descriptive and explanatory and in terms of the procedures a case study. The results were treated by Bardin's (1977) content analysis, collected through the mixed portfolio, guided by the teacher and the questionnaire answered by the students. We realized that the use of the portfolio is feasible in high school and consequent in other levels of education, both as a methodological and evaluative instrument. It is characterized as a possibility of formative assessment, which demonstrates the organization and progress of students at a conceptual level, in addition to respecting autonomy, stimulating creativity and reflective capacity and respecting the individuality of subjects.
Keywords: Ciências da Natureza; Portfólio; Avaliação da aprendizagem; Avaliação Formativa; Ensino Médio; Natural Sciences; Learning assessment; Formative assessment; High school; CNPQ::CIENCIAS EXATAS E DA TERRA